Machine learning analysis of extreme events in optical fibre modulation instability - Mikko Närhi; Lauri Salmela; Juha Toivonen; Cyril Billet; John M. Dudley; Goëry Genty (Nature Communications, 2018)
Real-time characterisation of nonlinear processes in the time domain is challenging. Here, Närhi et al. show that machine learning techniques can help overcome this limitation and use them to infer time-domain properties of optical fibre modulation instability from spectral intensity measurements.